RASPBERRY AS A POTENTIAL COMMODITY EXCHANGE MATERIAL IN THE REPUBLIC OF SERBIA - Dragan Gradimir Stojkovic; Fatima Živić; Milko Štimac; Katarina Borisavljevic; Nenad Grujovic (Ekonomika Poljoprivrede (1979), 2020)
Commodity exchange has a very long tradition and in a modern business conditions. Serbia ranks among the worlds largest producers of raspberries, exporting more than 90% of total production of this fruit. Considering that Serbia is among global leaders in the export of frozen raspberries and that the process of standardization of the quality and quantity of this type of fruit is relatively simple, the starting hypothesis is that Serbian raspberry can be traded at commodity exchange. The main objective of our research is to analyze the necessary conditions for formation and sustainable functioning of the raspberry commodity exchange, with the emphasis on testing the proposed model of the commodity exchange method of communication between primary raspberry producers (vendors), intermediaries (purchasers, raspberry dealers or exporters of raspberries) and end customers who buy raspberries. We surveyed 100 persons representing the key actors of the Serbian raspberry producers and proposed the model of raspberry trading through commodity exchange.